Um estudo sobre o uso do mecanismo de dicas no ensino de conceitos básicos de programação - Gonzalez, Gustavo Correia (2017)
Context: The high level of reprobation in subjects where basic programming concepts are taught at any level of education is a problem faced by many students and has been the subject of a number of researches. There are a number of reasons that are related to the origin of the problem, such as the teaching and learning method, the lack of some skills and interest on the part of the students, and the difficulty of the subject itself. To address this problem, systems that aid learning with hints are being used to help students perform exercises. Objective: The objective of this work was to develop an open source hints system to help students learn basic programming concepts, more specifically on condition structure and loop repetition topics. Method: The hints system, called iHint, was developed with the Laravel development framework. It was evaluated in a study with students and professionals of the Computing area from a set of previously defined exercises. The study was divided in 3 stages, being the first two destined to fill the base of hints of the system. In these stages, students who already did the subjects of algorithms and data structures and professionals of the Computing area participated. In the third stage of the study, students of the first period used the system to solve exercises using the previously registered hints. After completing these steps, through the data captured in the submissions, the measures related to the codes and the use of the hints for resolving the exercises were extracted. The third stage students also answered a questionnaire about the use of the tool. Results: 79 hints were created and 243 submissions were made in the study. Considering the participants of the third stage of the study, there are indications that the hints were useful to solve the first exercises. The results of the questionnaire indicate that the experience of using the system of hints was positive and that the hints were useful for the development of the exercises. However, the number of participants and exercises solved for the last stage of the study does not allow a more rigorous evaluation of the results and the tool. Conclusions: In this work, a system of hints was developed, reporting its main characteristics and evaluating it with students and professionals of the Computing area. From the evaluation performed after the application of the study, it was possible to identify indications that the use of the mechanism of hints helped the students in the resolution of exercise that approach basic concepts of programming.